A Penyuluhan CTPS dan konsumsi buah-sayur pada anak-remaja di kelurahan Asanno RT 003/RW 004: Penyuluhan kesehatan mengenai CTPS dan konsumsi buah-sayur ditatanan rumah tangga lebih khusus pada anak-remaja di kelurahan Asanno RT 003/RW 004 - Matulessy, Daniela; B. Ayomi, Mina; Kambuaya, Febi (Poltekkes Kemenkes Kendari, 2024)
Washing hands with soap and consuming fruits and vegetables are indicators of PHBS (Clean and Healthy Living Behavior) in the household setting. This outreach activity aims to increase the knowledge of children and teenagers about the importance of washing hands with soap (CTPS) and consuming fruits and vegetables to maintain health. The outreach method combines lectures, Q&A sessions, and the use of visual media such as posters. The posters contain the correct steps for washing hands with soap and running water, as well as the benefits of consuming fruits and vegetables. This combination of methods helps to convey health messages in an engaging and easily understandable way for children and teenagers. The results of the outreach activity show an increase in knowledge and understanding among children and teenagers, as evidenced by their ability to correctly answer the statements we provided. Therefore, this activity needs to be conducted regularly to ensure continuous understanding, thereby helping to prevent diseases and promote a healthy lifestyle within the household.